1991
DOI: 10.1002/bit.260371015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium osmolarity on hybridoma growth, metabolism, and antibody production

Abstract: Osmolarity is an important process variable during the cultivation of mammalian cells in vitro. Cell culture medium is designed to have osmolarity in the range of 260 and 320 milliosmoles (mOsm), basically to mimic the osmolarity of serum at 290 mOsm/kg. Fragmented information on the response of hybridoma cells to elevated osmolarity is available. A decrease in cell growth and an increase in antibody production were reported at high o~molarities.~~ Influence of osmolarity on antibody productivity seems to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
108
1
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 9 publications
24
108
1
2
Order By: Relevance
“…However, because hyperosmotic pressure suppresses cell growth, the enhanced q Ab of hybridoma cells in a hyperosmolar batch culture does not result in a substantial increase in the final antibody concentration Oh et al, 1993Oh et al, , 1995Ozturk and Palsson, 1991;Øyaas et al, 1994a, 1994bReddy and Miller, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…However, because hyperosmotic pressure suppresses cell growth, the enhanced q Ab of hybridoma cells in a hyperosmolar batch culture does not result in a substantial increase in the final antibody concentration Oh et al, 1993Oh et al, , 1995Ozturk and Palsson, 1991;Øyaas et al, 1994a, 1994bReddy and Miller, 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Each addition of 10× DMEM concentrates resulted in a significant increase in medium osmolality. The final medium osmolality reached up to 540 mOsm/kg which is known to be lethal to most hybridomas (Bibila et al, 1994;Oh et al, 1993;Øyaas et al, 1994;Ozturk and Palsson, 1991;Reddy et al, 1992;Reddy and Miller, 1994;Ryu and Lee, 1997). Figure 2 shows the results of fed-batch culture using a hypoosmolar medium (223 ± 3 mOsm/kg) as an initial basal medium.…”
Section: Resultsmentioning
confidence: 97%
“…A number of studies have shown that hypertonic stress can increase the specific MAb productivity of hybridoma cells (Oh et al, 1993;Øyaas et al, 1994a;1994b;Ozturk and Palsson, 1991;Reddy et al, 1992;Reddy and Miller, 1994;Yang et al, 1996). This has been attributed in part to increased amino acid uptake via the Na + -dependent symport (Oh et al, 1995).…”
Section: Introductionmentioning
confidence: 99%